Case of autoimmune hepatitis with overlap systemic lupus erythematosus. Issue 12 (29th December 2020) - Goyes, Daniela; Malladi, Vijayram R; Ishtiaq, Rizwan; Al-Khazraji, Ahmed
Abstract : Autoimmune hepatitis (AIH) is an autoimmune liver disease characterised by the presence of autoantibodies including antinuclear antibodies, anti-smooth muscle antibody and hypergammaglobulinaemia. Systemic lupus erythematosus (SLE) is a systemic disease that can affect multiple organs. Coexistence of AIH and SLE as an overlap syndrome occurs in about 1%–2.6% of the AIH cases. Since both conditions share common autoimmune features, their coexistence can pose a diagnostic dilemma which can result in a delay in treatment. We present here a challenging case of a middle-aged woman with AIH in remission who later developed new-onset fatigue, pleural effusion and splenomegaly.